The Implication of Cooperative Integrated Reading and Composition (CIRC) Technique on English Reading Comprehension for Madrasah Aliyah Students - M. Arif Rahman Hakim; Pengky Kemadi Amrulin; Fera Zasrianita; Yuda Septian Kurniawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The objective of this study was to find out whether or not there was an effect of the Cooperative Integrated Reading and Composition (CIRC) Technique on Students Reading Comprehension in understanding the Narrative text at MA Pancasila Bengkulu City. In this study, researcher used a Quasi Experimental research nonequivalent pretest-posttest control group. The population of this research was the tenth grade students at MA Panacasila Bengkulu. The sample was X MIPA.1 which was treated as experimental class and taught by using CIRC Technique and X MIPA.2 was treated as control class and taught by using conventional strategy. There were 30 students who were sampled as 19 experimental classes and 19 control classes. To determine the sample, the researcher used Total sampling technique. In the process of data collection, researcher used test and documentation as research instruments. The test take form of multiple choice containing 20 questions. Test is given to both experimental and control classes as pre-test and post-test. The data from the pre- test and post-test were examined using the t-test. The result of this research showed that students reading comprehension test for the experimental class's mean score was 54.21, while the control class was 44.47, and for post-test findings reveal that the experimental class has an average value of 80.79, while the control class has an average value of 71.58. The hypothesis test results show that the output of the independent sample t-test (sig. 2-tailed) is 0.001 which is lower than 0.05. So, Ho was rejected and Ha was accepted. In brief, it can be concluded that Cooperative Integrated Reading and Composition (CIRC) Technique can be one of effective ways in teaching reading for tenth grade students in Madrasah Aliyah level. Keywords: Cooperative Integrated Reading and Composition (CIRC), Madrasah Aliyah, Narrative Text Reading Comprehension